PERAN FORUM KOMUNIKASI ANAK KOTA BANDUNG MELALUI PROGRAM PANGLIMA DALAM MEMBANGUN KESADARAN ANTI-BULLYING (Studi Kasus Sekolah Dasar Swasta As-Salam) - Hilda Fadilah; Diah Gusrayani; Dety Amalia Karlina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to evaluate the socialization strategies carried out by the Forum Komunikasi Anak Kota Bandung (FOKAB) through the PANGLIMA program as an effort to prevent bullying in elementary schools. The research employs a qualitative approach with a case study method. Data were collected through in-depth interviews, observations, and document analysis. The research informants consisted of FOKAB administrators and facilitators, teachers at SDS As-Salam, and elementary school students. The findings show that the PANGLIMA socialization strategy was designed in a creative and contextual manner through role-playing methods, the use of visual media, and the symbolic approach of